Dynamics And Statics of Neologisms in The Modern Russian Language on The Example of Mass Media (Eurasian Journal of Engineering and Technology, 2023)
The pragmatic functions of neologisms in modern media are analyzed and considered, certain connections between pragmatics and active nomination processes are comprehended, the functioning of Russian neologisms in journalistic texts in a combination of stylistic and pragmatic aspects is described. It is proved that the authors of journalistic texts use neologisms as a communicative strategy to achieve their communicative goals. Neologisms can perform various functions, in particular, nominative, but to a greater extent they are able to express the subjective assessment of the author. The emergence of a new word is closely related to the social need for a particular lexical unit.